Adaptive changes induced by noble-metal nanostructures in vitro and in vivo - Huang, Qianqian (Theranostics, 2020)
The unique features of noble-metal nanostructures (NMNs) are leading to unprecedented expansion of research and exploration of their application in therapeutics, diagnostics and bioimaging fields. With the ever-growing applications of NMNs, both therapeutic and environmental NMNs are likely to be exposed to tissues and organs, requiring careful studies towards their biological effects in vitro and in vivo. Upon NMNs exposure, tissues and cells may undergo a series of adaptive changes both in morphology and function. At the cellular level, the accumulation of NMNs in various subcellular organelles including lysosomes, endoplasmic reticulum, Golgi apparatus, mitochondria, and nucleus may interfere with their functions, causing changes in a variety of cellular functions, such as digestion, protein synthesis and secretion, energy metabolism, mitochondrial respiration, and proliferation. In animals, retention of NMNs in metabolic-, respiratory-, immune-related, and other organs can trigger significant physiological and pathological changes to these organs and influence their functions. Exploring how NMNs interact with tissues and cells and the underlying mechanisms are of vital importance for their future applications. Here, we illustrate the characteristics of NMNs-induced adaptive changes both in vitro and in vivo. Potential strategies in the design of NMNs are also discussed to take advantage of beneficial adaptive changes and avoid unfavorable changes for the proper implementation of these nanoplatforms.